Anti-Inflamatory Effect Of Aquadest Extract Of Mango Ginger Rhizome (Curcuma mangga Val) In Swiss Webster Mice (Mus musculus) - Damaryan, Difa; Tibrani, Masagus Muhammad; Riyanto (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2025)
This study aims to determine the effect of aqueous extract of Curcuma mangga Val. rhizome on the anti-inflammatory response in mice (Mus musculus). The study employs an experimental method with a completely randomized design (CRD) consisting of five treatment groups: a negative control (aqueous solution), a positive control (Sodium Diclofenac 0.13 mg/kgBW), and three doses of Curcuma mangga rhizome extract (7 mg/kgBW, 28 mg/kgBW, and 56 mg/kgBW). Each treatment was administered orally 15minutes before induction with 1 % of egg white. The mice's edema volume was measuredevery hour for six hours after inflammation induction using egg white. Data were analyzed using One-Way ANOVA and Duncan's Multiple Range Test (DMRT). The One-Way ANOVA results indicated a significant effect of Curcuma mangga aqueous extract on the anti-inflammatory response, while the DMRT results showed that the 56 mg/kgBW dose had the most significant anti-inflammatory effect, with an edema inhibition percentage of 63%, closely approaching the effectiveness of Sodium Diclofenac at 62%.